Intradural extramedullary granular cell tumour in a cat. (10th May 2018) - Valentini, A.; Canal, S.; Mandara, M. T.; Balducci, F.; Bernardini, M.
Abstract : A 7‐year‐old domestic shorthair cat was evaluated for progressive paraparesis, inability to jump, a paralysed tail and inability to void the bladder. Neurologic examination was consistent with a L4‐S3 localisation. Survey radiographs of the lumbar vertebral column revealed L4‐L7 vertebral body remodelling. A pre‐contrast T1‐weighted hyperintense, diffusely enhancing intradural lesion extending from L4 to S1 vertebral bodies was detected by MRI. Large, mesenchymal, round‐to‐polygonal cells arranged in nests or sheets were found on histologic examination at post mortem . These cells were characterised by abundant intracytoplasmic PAS‐positive, diastase‐resistant granules and positive immunoexpression of vimentin, S‐100, neuron‐specific enolase and desmin. This is the first report of a spinal granular cell tumour in a cat.